Den svenska gymnastiken i Spanien: Två spanjorers resa till Stockholm 1910 för att studera linggymnastik vid Gymnastiska Centralinstitutet - Jäppinen, Karin; Eduardo J. , Aragón Gómez (Idrott, historia och samhälle, 2026)
In 1910, two young professors from the Infantry Academy in Toledo traveled to Stockholm to study the methods of Swedish gymnastics at the Gymnastics Central Institute (GCI). Their names were First Medical Officer Federico González Deleito and Infantry Captain Federico Gómez de Salazar y Orduña. In this article, we have tried to follow the Spaniards during their studies in Stockholm, their teachers and classmates, and what they brought back as inspiration from Swedish gymnastics to develop military gymnastics in Spain after their return.